The Effect of Substrate Mixture Ratio on Biogas Volume in Co-digestion of Water Hyacinth (Eichhornia crassipes) and Cow Manure through Anaerobic Digestion - Aziz, Ahmad Musonnifin; Dhaniswara, Trisna Kumala; Azizah, Zahrotul; Ferdiansyah, Ferdiansyah; Proboncono, Dharma Putra; Faris, Achmad (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2025)
Biogas is a renewable energy source that can be produced from organic waste, such as water hyacinth and cow dung. Utilizing these two materials through co-digestion has the potential to increase biogas production due to a better nutrient balance. This study aims to analyze the effect of the substrate ratio on the volume of biogas produced through anaerobic digestion. The method used is a Systematic Literature Review (SLR) by reviewing five relevant scientific articles based on certain inclusion and exclusion criteria. The parameters analyzed include the substrate ratio, biogas volume, and hydraulic retention time (HRT) or fermentation duration. The results of the study indicate that the substrate ratio has a significant influence on biogas production. Ratios that are close to balance, such as 50:50 and 47:53, tend to produce more optimal and stable biogas volume. Conversely, unbalanced ratios, such as 33:67, show varying results depending on operational conditions. Differences in biogas volume between studies are also influenced by other factors, such as retention time, raw material characteristics, and process conditions such as pH and temperature. The lignocellulose content of water hyacinth can inhibit the degradation process if not balanced with an adequate nitrogen source from cow dung. In conclusion, a balanced substrate ratio plays a crucial role in increasing biogas production, but it needs to be supported by controlling other operational parameters to achieve optimal and sustainable results.